2018
DOI: 10.4000/educationdidactique.3041
|View full text |Cite
|
Sign up to set email alerts
|

Le manuel scolaire : une ressource au « statut paradoxal »

Abstract: The textbook: a resource with a « paradoxical status ». Elementary school teachers' relationship to the mathematical textbook Mots-clés : manuels scolaires, mathématiques, école élémentaire en France, pratiques enseignantes, offre éditoriale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Such attitudes are often encountered among teachers because, voluntarily or not, they are part of the debate regarding the quality of textbooks and their usage in the classroom. Some researchers (Castro, 2011;Priolet & Mounier, 2018) have concluded that the teachers′ attitudes towards textbooks are ambiguous: Some consider textbooks indispensable, while others deem them superfluous. Many teachers would prefer to banish textbooks for good, and the rest are indifferent.…”
Section: Introductionmentioning
confidence: 99%
“…Such attitudes are often encountered among teachers because, voluntarily or not, they are part of the debate regarding the quality of textbooks and their usage in the classroom. Some researchers (Castro, 2011;Priolet & Mounier, 2018) have concluded that the teachers′ attitudes towards textbooks are ambiguous: Some consider textbooks indispensable, while others deem them superfluous. Many teachers would prefer to banish textbooks for good, and the rest are indifferent.…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons alors développé un travail portant sur l'analyse des propositions d'enseignement de notions géométriques faites dans les manuels scolaires (papier) dans le cadre des programmes français d'enseignement à l'école primaire (Guille-Biel Winder et Petitfour, 2018). Ce travail se situe en amont de questions étudiées dans d'autres recherches sur les manuels scolaires, comme la prise en compte de la variabilité des pratiques effectives des professeurs des écoles utilisant un même manuel (Arditi, 2011), l'étude de la place du manuel dans l'activité enseignante (Priolet et Mounier, 2018) ou bien encore l'usage que les élèves font de ces manuels (Rezat, 2012). Puisqu'en France le cycle 3 est une période importante pour les apprentissages géométriques, nous avons choisi de nous intéresser au niveau CM1 (9-10 ans), première année de ce cycle, et de centrer notre étude sur l'enseignement du thème « perpendicularité et parallélisme », notions qui apparaissent à ce niveau-là dans les programmes scolaires.…”
unclassified